Regulasi emosi dalam dunia pendidikan: Analisis bibliometrik dalam satu dekade - Ziyadatulkhair, Rochmat (Maliki Interdisciplinary Journal, 2025)
This study analyzes research trends on emotion regulation in education using a bibliometric approach. Data were collected from Scopus metadata spanning 2014–2024 and processed using the Biblioshiny software. The results indicate a peak in annual scientific production in 2018, followed by a significant decline after 2021. A keyword network analysis reveals the centrality of "emotion regulation" and its connections to topics such as mental health, stress, and parenting, along with its relevance to social contexts like the COVID-19 pandemic. Topic trends highlight the prominence of research on mindfulness, emotion regulation, and mental health. The decline in scientific publications may be attributed to shifting research priorities or funding limitations. This study underscores the importance of emotion regulation in education to foster supportive learning environments, particularly when addressing global challenges. The authors recommend further exploration of emotion regulation in the context of special needs education and its impact on educators and students in the post-pandemic era.